THE USE OF YOUTUBE AS A LEARNING MEDIUM TO IMPROVE SPEAKING SKILLS IN HIGHER EDUCATION - Amrina Amrina; Asyatilla Novandra Adrita; Krim Ulwi (Yayasan Adra Karima Hubbi, 2026)
Students' learning motivation has recently declined because teachers have limited control over the learning environment, even though many references are now available as guidelines or sources for introducing learning materials, including YouTube-based resources. This study aimed to examine the use of YouTube-based media and learning in relation to students' learning motivation. A quantitative method was employed; data were obtained through interviews and questionnaires, with the questionnaires distributed online. The findings showed that YouTube-assisted learning media could increase students' learning motivation, as reflected in improved learning outcomes. This study concluded that using YouTube as a learning medium was effective and efficient, as demonstrated by the finding that 90% of students obtained the highest scores. The study was limited to the YouTube learning environment, although many other learning environments could be used to improve students' speaking skills. Future researchers are expected to conduct studies related to students' learning motivation by using different learning environments. This study also recommends that future researchers investigate learning motivation through YouTube.